A PRAGMATICS OF CIVIC ENGAGEMENT AN ANALYSIS OF OBASANJO’S LETTERS - Iredele, Tolulope (International Journal of Language and Literary Studies, 2021)
The study investigates the role of language in civic engagement and demonstrates how language is used as a viable tool to propel civic actions. Hence, it focused on the locution and illocutionary acts of Obasanjo’s letters to two presidents in Nigeria. Sixty sentences were selected from three open letters. The findings showed that the overall relative frequency percentages are: commissive 15%, assertive 20%, directive 48.3%, declarative 6.7%, and expressive 10%. Results show that Obasanjo, in his letters relied more on sentences that performed directive acts more than other speech acts. However, in his letters to Buhari, he used sentences with assertive acts more than he used in his letter to Jonathan. Hence, the data is characterized by a preponderance of directive, assertive and commissive acts as rhetoric strategies. The study confirms that language use in political discourse is rarely neutral. It further demonstrates that civic engagement drivers manipulate language to influence political decisions and reconstruct public opinion by propelling certain actions or inactions.